Bauran Pemasaran Kacang Shanghai Jessivar Di Kelurahan Talikuran Barat Kecamatan Kawangkoan Utara Kabupaten Minahasa - Pioh, Geby Karla; Jocom, Sherly Gladys; Laoh, Olly Esry Harryani (AGRI-SOSIOEKONOMI, 2024)
This study aims to describe the marketing mix of Jessivar shanghai beans in Talikuran Barat Village, Kawangkoan Utara District, Minahasa Regency. This research was conducted from May to July 2023. The selection of respondents was done intentionally. The data used are primary data and secondary data. Primary data was obtained from respondents through direct interviews using a prepared questionnaire. Secondary data was obtained from other information data related to the research. The sampling method used purposive sampling, and the samples taken were 1 Jessivar shanghai bean business owner as a producer and 17 kiosk owners in the Kawangkoan area as consumers who bought shanghai beans at the Jessivar shanghai bean business. The results showed that the Jessivar shanghai bean marketing mix has a good assessment by consumers as seen from the total overall score of 540 with an interpretation of 88.23 percent being in an agreed assessment based on aspects of product, price, place, promotion, and there are several variables that must be considered and improved such as the use of promotional media and business locations that are easily accessible to consumers.